Ultrasound Findings of Intraductal Papillary Neoplasm in Bile Duct and the Added Value of Contrast-Enhanced Ultrasound - Liu, L. N.; Xu, H. X.; Zheng, S. G.; Sun, L. P.; Guo, L. H.; Zhang, Y. F.; Xu, J. M.; Liu, C.; Xu, X. H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To investigate the imaging features of intraductal papillary neoplasm in bile duct (IPNB) on baseline ultrasound and contrast-enhanced ultrasound (CEUS).Materials and Methods: The imaging features on baseline ultrasound and CEUS in 16 pathologically proven IPNB lesions in 15 patients were retrospectively analyzed. Real-time contrast specific modes and contrast agent of SonoVue were used for CEUS.Results: Bile duct dilation was present in all patients. The mean lengths for the intraductal papillary adenomas and adenocarcinomas were 2.5 ± 1.1 (range, 1.2 – 4.2 cm) and 5.6 ± 2.0 cm (range, 3.3 – 9.8 cm) (P = 0.004). Three imaging types of IPNB on ultrasound were depicted: bile duct dilation with intraductal mass (n = 8), bile duct dilation without intraductal mass (n = 3), and cystic-solid mixed type (n = 5). On CEUS, solid components of 13 lesions appeared hyper- (n = 12) or iso-enhancement (n = 1) in the arterial phase whereas all showed hypo-enhancement in the portal and late phases. For 3 lesions of bile duct dilation without intraductal mass, CEUS showed non-enhancement during all phases. Pre-surgical CEUS and conventional ultrasound made correct diagnoses in 12 (75.0 %) and 5(31.3 %) of 16 IPNBs respectively (P = 0.04). For CECT, correct diagnosis was also achieved in 12 (75.0 %) of 16 lesions (P = 1.00, in comparison with CEUS).Conclusions: IPNB should be taken into consideration when intraductal mass or cystic-solid mass with bile duct dilation, or remarkable bile duct dilation without intraductal mass, are found on US. Intraductal mass length > 3.0 cm is more commonly found in malignant IPNB. CEUS might facilitate the diagnosis of IPNB by easily excluding the possibility of commonly found sludge, nonshadowing stones, or blood clots.
Keywords: abdomen; ultrasound 2 D; contrast agents